Critical perspectives on literature and culture in the new world order - Noritah Omar; Washima Che Dan; Jason Sanjeev Ganesan; Rosli Talif (Cambridge Scholars Publishing, 2010)
The papers in 'Critical Perspectives on Literature and Culture in the New World Order' were originally presented at the 4th Malaysia International Conference on Languages, Literatures and Cultures (MICOLLAC) 2005, in Kuala Lumpur, Malaysia. The fifteen chapters in this volume explore both new and tested theoretical perspectives on literature and culture at large; this multiplicity of discourses is a reflection of the implicit discontent in conforming to the New World Order, and a contestation against hierarchical relationships between countries, which inform the social, cultural and political climates of weaker nations. With the political and economic hegemony of stronger nations, weaker nations run the risk of being dominated, or at the very least, having their own national identity and sovereignty steeped in ambivalence in the face of a globalised culture. This volume hopes to bring together critical views in relation to the construction of cultural studies in the Western framework, the application of literary theory in the readings of vernacular literature, contestation of the mainstream scientistic methodology of cultural evaluation, the role of English literature in Asian cultures, the application of postcolonial theory in literature, literary ethics in relation to Islamic literature, as well as the Islamic and Western conceptions of democracy. More than half of the articles in this collection centre on Islam as a guiding principle, or as a context through which critical perspectives are made on literature and culture in today's globalised world order. This inadvertent foregrounding of Islam reflects a continuing dialogue on and with Islam and its significant impact on existing academic discourses founded upon Western-style scholarship.